EFEKTIVITAS PEMBELAJARAN PASSING BAWAH BOLAVOLI UNTUK KELAS X DENGAN PENGGUNAAN MEDIA AUDIO VISUAL - YULIAS P, IDIN (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The purpose of this study was to determine the effectiveness of learning passing volleyball for class X with the use of audio-visual media. This type of research is experimental research. The instruments will be used: 1) students' opinions FCE, 2) observations (observation), 3) assessment of mastery of learning outcomes, 4) passing the test with a wall volley volleyball. Based on the results obtained penjaskes learning effectiveness by using audio-visual media in the opinion of FCE students, showed good category. (2) the effectiveness of learning penjaskes using audiovisual media based on the observation (observation) of teachers and students, showed good category. (3) the effectiveness of learning penjaskes using audiovisual media based assessment of student mastery of learning outcomes include: aspects of psychomotor, cognitive and affective outcomes showed good category. (4) the effectiveness of learning by penjaskes wall volley test can be said that: passing the volleyball learning using audio-visual media to give a positive increase in students by 3.78 or 19.53%. Different test results mean for paired samples showed that tcount 4.311> 2.042 ttable value. Then it can be concluded that there are significant differences between the volleyball passing skills of students before and after the application of learning by using audio-visual media. Keywords: effectiveness, audiovisual media, passing under volleyball